2020
DOI: 10.5194/acp-20-7069-2020
|View full text |Cite
|
Sign up to set email alerts
|

Volatile organic compounds and ozone air pollution in an oil production region in northern China

Abstract: Abstract. Oil and natural gas (O&NG) exploration presents a significant source of atmospheric volatile organic compounds (VOCs), which are central players of tropospheric chemistry and contribute to formations of ozone (O3) and secondary organic aerosols. The impacts of O&NG extraction on regional air quality have been investigated in recent years in North America, but have long been overlooked in China. To assess the impacts of O&NG exploration on tropospheric O3 and regional air quali… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
60
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 81 publications
(71 citation statements)
references
References 65 publications
(91 reference statements)
11
60
0
Order By: Relevance
“…Tai were substantially lower than those derived from most of the ground-level sites over China, such as Beijing (Liu et al, 2012;Yang et al, 2018), Wuhan (Lu et al, 2017), Chengdu (Tan et al, 2018), Hong Kong (Xue et al, 2016;Z. Li et al, 2018), and a rural site in the Yellow River Delta region (Chen et al, 2020). Note that most of these previous studies were based on modeling of the polluted photochemical episodes, but the modeled highest RO x production rates at Mt.…”
Section: Impacts Of Hono On Oh Radical and Atmospheric Oxidation Capamentioning
confidence: 87%
See 1 more Smart Citation
“…Tai were substantially lower than those derived from most of the ground-level sites over China, such as Beijing (Liu et al, 2012;Yang et al, 2018), Wuhan (Lu et al, 2017), Chengdu (Tan et al, 2018), Hong Kong (Xue et al, 2016;Z. Li et al, 2018), and a rural site in the Yellow River Delta region (Chen et al, 2020). Note that most of these previous studies were based on modeling of the polluted photochemical episodes, but the modeled highest RO x production rates at Mt.…”
Section: Impacts Of Hono On Oh Radical and Atmospheric Oxidation Capamentioning
confidence: 87%
“…However, the contributions of the individual surface types to ambient HONO formation have not been figured out. Most previous studies have suggested the dominance of the ground surface in heterogeneous HONO formation at the ground level (Alicke et al, 2003;Elshorbany et al, 2009;Ziemba et al, 2010), while some studies have argued that aerosol surface may also play an important role (Colussi et al, 2013;Liu et al, 2014;Tong et al, 2016;Lu et al, 2018)…”
Section: Introductionmentioning
confidence: 99%
“…The applied homogeneous chemical mechanism was the state-of-the-art MCM version 3.3.1 (MCMv3.3.1; http://mcm.leeds.ac.uk/MCM/; Jenkin et al, 2003;Saunders et al, 2003), which near-explicitly describes the reactions of 143 VOC species and has been widely used to reproduce the nonlinear chemistry between O 3 and its precursors in the atmosphere (Chen et al, 2020;Xue, Wang, Gao, et al, 2014). In addition to homogeneous chemistry, heterogeneous chemistry including N 2 O 5 hydrolysis, HO 2 loss on aerosols, and HONO formation from NO 2 surface reactions were also considered in this model (Xue et al, 2016;Xue, Wang, Gao, et al, 2014).…”
Section: Lagrangian Photochemical Trajectory Modelmentioning
confidence: 99%
“…Several studies have examined O 3 pollution characteristics, formation regimes, and source apportionment (Wang, Xue, et al, 2017;and references therein). In summer, high O 3 episodes (defined in this study as a maximum daily 8-h average O 3 mixing ratio (MDA8 O 3 ) that exceeds 75 ppbv) have occurred frequently in various environments covering urban, suburban, rural, and mountainous sites (Chen et al, 2020;Lyu et al, 2019;Ma et al, 2019;Sun et al, 2016;Wei et al, 2015;Zong et al, 2018). The maximum hourly O 3 concentration at a rural site downwind of Beijing reached as high as 286 ppbv in June-July 2005 (Wang et al, 2006) and long-term trend analyses have confirmed the rapid increase of regional O 3 concentrations (Sun et al, 2016(Sun et al, , 2019Xu et al, 2020).…”
mentioning
confidence: 99%
See 1 more Smart Citation